Erythrina leafminer (suggested common name); Leucoptera erythrinella Busck, 1900 (Insecta: Lepidoptera: Lyonetiidae) - Andrei Sourakov (EDIS)
The erythrina leafminer is a member of the genus Leucoptera, which are leaf borers that can cause severe damage to plant crops, such as coffee or apples. Even though these moths are 1/20 to 1/10 the size of an average moth, they can cause serious damage. Leucoptera erythrinella is a pest of the coral bean and other members of the genus Erythrina. The larvae feed inside the leaves, making elaborate and characteristic mines, which from a distance appear to be discolorations of the leaf itself. This 5-page fact sheet was written by Andrei Sourakov, and published by the UF Department of Entomology and Nematology, January 2014.